Cognitive behavioral therapy for insomnia in Parkinson’s disease: a case series - Meghan Humbert (Nature Portfolio, 2017)
Abstract Chronic insomnia is common in patients with Parkinson’s disease. There are limited data to guide its treatment in this patient population, especially in regards to non-pharmacologic interventions, some of which are highly effective in the non-Parkinson’s disease population. The aim of this study is to describe a series of Parkinson’s disease patients who underwent cognitive behavioral therapy for insomnia (CBTi). Parkinson’s disease patients who had undergone a baseline and at least one follow-up CBTi session were identified. Electronic medical records and pre-treatment and post-treatment patient sleep diaries were reviewed. Sleep measures of interest included wake time after sleep onset, sleep efficiency, sleep onset latency, and total sleep time. Pre-treatment and post-treatment values were compared within subjects using paired t-test. Five patients were included. Patients attended an average of eight sessions of CBTi (range 5–12). Significant increases in sleep efficiency (p = 0.02) and decreases in number of awakenings per night (p = 0.02) were found. Our data provide preliminary evidence that cognitive behavioral therapy is an effective treatment for insomnia in Parkinson’s disease, and is well tolerated and well received by patients. Given the limited data supporting use of medications to treat chronic insomnia in Parkinson’s disease, combined with their risks, randomized trials to demonstrate the efficacy of CBTi in Parkinson’s disease are warranted.